Nano-encapsulation and characterization of baricitinib using poly-lactic-glycolic acid co-polymer - Mohammad Javed Ansari; Saad M. Alshahrani (Elsevier, 2019)
Baricitinib is a recently approved anti-rheumatic drug having very poor aqueous solubility and hence its performance suffers from low or inconsistent oral bioavailability. The purpose of the study was to develop and evaluate poly lactic-co-glycolic acid (PLGA) nanoparticles of baricitinib in order to enhance in vitro dissolution and performance. Nano-suspension of baricitinib with or without PLGA, a biodegradable, FDA approved semi-synthetic polymer, was developed by nanoprecipitation method. Research methodology employed a quantitative research utilizing experimental design wherein effect of independent variables such as amount of polymer, drug: polymer ratio, types of solvent, and solvent: anti-solvent ratio were evaluated over the size and size distribution of nanoparticles along with entrapment efficiencies. Among the several organic phases evaluated, acetone was found to be suitable solvent for drug and polymer. The aqueous phase (anti-solvent) was deionized water containing 1% w/v pluronic 127 as the stabilizer of nanoparticle suspension. The optimized nanoparticles had particle size less than 100 nm (91 nm ± 6.23) with a very narrow size distribution (0.169 ± 0.003), high zeta potential (−12.5 mV ± 5.46) and entrapment efficiency (88.0%). The optimized nanoparticles were characterized by scanning electron microscopy, X-ray diffraction, differential scanning calorimetry, infrared spectroscopy and in vitro dissolution studies. In-vitro dissolution study of PLGA nanoparticles exhibited sustained release with approximately 93% release of baricitinib during 24-h period. Keywords: Baricitinib, Nanoparticles, Nanoprecipitation, Encapsulation, Solubility, Dissolution